Tradisi Megoak-Goakan Sebagai Media Penguat Karakter Berbasis Kearifan Lokal Di Era Industri 4.0 - Ni Putu Candra Prastya Dewi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Along with the development of technology in the industrial era 4.0, there is also a growing foreign culture going to Indonesia. But people need to preserve the wisdom of local culture by studying their own culture. One of the cultures in Bali is the Megoak-goakan tradition. Megoak-goakan is a tradition held by the people of Panji village, Sukasada District, Buleleng Regency. This tradition was carried out as a form of respect for Ki Gusti Panji Sakti, King of Buleleng. The cultural tradition is still developing until now in the form of traditional games that were held on the day of Ngembak Geni the day after Nyepi. There are cultural values ​​in the tradition of mutuality, namely religious values, the value of unity, socio-cultural values, and the value of mutual cooperation. This Megoak-goakan tradition instills character in the community, namely religious character, mutual cooperation, nationalism, integrity, and independence. The implementation of the tradition of Megoak-goakan in the form of traditional games can be carried out in schools to instill character in students or in the community to reduce the negative behavior of the community, thereby creating a peaceful and upholding community. So it can be concluded that Megoak-goakan can be a local wisdom-based character reinforcement media in the face of the swift flow of globalization due to technological developments in the industrial era 4.0.